a²b×1/9a²b³+2/3a⁵b⁴ ÷(-3a)-(a²b³)² ÷ (-1/2b²)-(2/3a⁴b²)³ ÷ (1/3a⁴b ) ²
va rog repede
dau coroana
![Ab19ab23ab 3aab 12b23ab 13ab Va Rog Repede Dau Coroana class=](https://ro-static.z-dn.net/files/d32/6143f23a1f0cf2dff6a2323d260904c2.jpg)
Răspuns:
[tex]\frac{14}{9} a^{4} b^{4}[/tex]
Explicație pas cu pas:
1/9 a^4b^4 - 2/3 a^5b^4 : 3a + a^4b^6 : b^2/2 - (1/3a^4b^2)^3/(1/3 a^4b)^2 =
1/9 a^4b^4 - 2/3 x a^5b^4/3a + a^4b^6 x 1/27 a^12b^6 / 1/9 a^8b^2 =
1/9 a^4b^4 - 2/3 x a^4b^4/3 + a^4b^4 x 2 - a^4b^4/3 =
1/9 a^4b^4 - 2a^4b^4/9 + 2a^4b^4 - a^4b^4/3 =
14/9 a^4b^4